The unbearable weight of massive talent [videorecording (DVD)] - Cage, Nicolas, 1965-; Pascal, Pedro; Horgan, Sharon, 1970-; Barinholtz, Ike, 1977-; Mastronardi, Alessandra, 1986-; Scipio, Jacob, 1993-; Sheen, Lily; Harris, Neil Patrick, 1973-; Haddish, Tiffany, 1979- (Lionsgate, 2022)
"Nicolas Case plays... Nick Cage! Creatively unfulfilled and facing financial ruin, the fictionalized version of Cage accepts a million-dollar offer to attend the birthday of a dangerous superfan. Things take an unexpected turn when Cage is recruited by a CIA operative and he must use his legendary acting skills, channeling his most iconic and beloved characters to become a real-life action hero" --Container.